Application of The Discovery Learning Model with a Thinking Approach to Improving Students' Activity on The Content Indonesian Language in Class III - Nurhidayana, Nurhidayana; Destrinelli, Destrinelli; Budiono, Hendra (FKIP - Universitas Riau, 2023)
This research was motivated by the low activity of class III students at SDN 83/1 Bajubang. This research is a Classroom Action Research which aims to describe the increase in student activity through the application of the Discovery Learning model with the MIKiR approach to Indonesian content in class III. This research was conducted at SDN 83/I Bajubang. Research data obtained by means of observation, interviews and also documentation. The data in this study were analyzed descriptively qualitatively. The results of the study show that applying the discovery learning model with the MIKiR approach to the learning process can increase student activity. This increase can be seen in the data analysis of each meeting cycle. Cycle I meetings I and II were 42.85%, cycle II meeting I was 66.66%, cycle II meeting II was 80% which increased by 13.34%. In this case it is concluded that the use of the discovery learning model with the MIKiR approach can increase the activity of students in Indonesian language content in class III SDN 83/1 Bajubang. Proven by the success of this research. The activeness of students can be increased by the discovery learning model with the MIKiR approach.